PENGARUH INTENSITAS ASET TETAP DAN LEVERAGE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016 – 2019 - Herry Winarto; Dici Oktaria (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study aims to examine the effect of Fixed Asset Intensity, and Leverage on Tax Avoidance in manufacturing companies in the Consumer Goods Industry sector listed on the Indonesia Stock Exchange in 2016-2019. The number of companies that were used as samples for this study were 10 companies using the purposive sampling method. While the data analysis method used is descriptive statistical test, classical assumption test, multiple linear regression analysis, simultaneous significance test (F test), individual parameter significance test (t test) and coefficient of determination. Based on the results of the study, it shows that the Intensity of Fixed Assets, Leverage, simultaneously has a significant effect on Tax Avoidance with a significance level of 0.004. While partially, Asset Intensity has a positive effect having a significance value of 0.007 and Leverage has a significant effect on Tax Avoidance having a significance value of 0.049